НЕПАРАЗИТАРНІ КІСТИ СЕЛЕЗІНКИ – ОРГАНОЗБЕРІГАЛЬНА ТАКТИКА ЛІКУВАННЯ - Євстахевич, І. Й.; Інденко, Ф. П.; Євстахевич, Ю. Л.; Семерак, М. М.; Книш, О. В.; Дяків, Г. Л.; Семерак, І. Я. (Українські медичні вісті, 2023)
НЕПАРАЗИТАРНІ КІСТИ СЕЛЕЗІНКИ – ОРГАНОЗБЕРІГАЛЬНА ТАКТИКА ЛІКУВАННЯ